Merchant ship construction especially written for the merchant navy - Pursey, H.J (Brown and Ferguson, 2002)
A thoroughly illustrated work discussing the construction, connections and uses of the various parts in ordinary ships and in oil tankers, the survey of ships and testing of materials, shipyard practice and a series of definitions.